No economic benefit of early knee reconstruction over optional delayed reconstruction for ACL tears: registry enriched randomised controlled trial data. Issue 9 (2nd March 2016) - Kiadaliri, Aliasghar A; Englund, Martin; Lohmander, L Stefan; Steen Carlsson, Katarina; Frobell, Richard B
Abstract : Background: To analyse 5-year cost-effectiveness of early versus optional delayed acute anterior cruciate ligament (ACL) reconstruction. Methods: 121 young, active adults with acute ACL injury to a previously uninjured knee were randomised to early ACL reconstruction (n=62, within 10 weeks of injury) or optional delayed ACL reconstruction (n=59; 30 with ACL reconstruction within 6–55 months); all patients received similar structured rehabilitation. Real life data on health care utilisation and sick leave were obtained from regional and national registers. Costs and quality-adjusted life years (QALYs) were discounted at 3%. Full-analysis set (based on study randomisation) and as-treated analysis (according to actual treatment over 5 years) principles were applied. Results: Mean cost of early ACL reconstruction was €4695 higher than optional delayed ACL reconstruction (p=0.19) and provided an additional 0.13 QALYs (p=0.11). Full-analysis set showed incremental net benefit of early versus optional delayed ACL reconstruction was not statistically significantly different from zero at any level. As-treated analysis showed that costs for rehabilitation alone were €13 650 less than early ACL reconstruction (p<0.001). Results were robust to sensitivity analyses. Conclusions: In young active adults with acute ACL injury, a strategy of early ACL reconstruction did not provide extra economic value over a strategy of optional delayed ACL reconstruction over a 5-year period. Results from this and previous reports of the KANON-trial imply that early identification of individuals who would benefit from either early ACL reconstruction or rehabilitation alone might reduce resource consumption and decrease risk of unnecessary overtreatment. Trial registration: ISRCTN84752559.